Virology molecular biology and pathogenesis - Norkin, Leonard C. (ASM Press, 2010)
"Based on the author's experiences teaching virology for more than 35 years, Virology: Molecular Biology and Pathogenesis enables readers to develop a deep understanding of fundamental virology by emphasizing principles and discussing viruses in the context of virus families. Moreover, individual virus families are examined within the context of the Baltimore classification system, a key unifying theme that allows readers to assume basic facts about the replication strategy of a virus based on the nature of its genome."